Anais Do III Inovagri International Meeting - 2015 2015
DOI: 10.12702/iii.inovagri.2015-a64
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade E Composição Botânica De Tifton 85 Nas Diferentes Estações Do Ano Sob Irrigação

Abstract: RESUMO: O objetivo do trabalho foi avaliar a produtividade e a composição botânica do capim Tifton 85 na presença e na ausência de irrigação durante as quatro estações do ano. O experimento foi conduzido no período de novembro de 2012 a maio de 2013, em uma propriedade de produção leiteira, localizada no município de Mariluz, região Noroeste do Paraná. O delineamento experimental utilizado foi de blocos casualizados em esquema de parcelas subdivididas, com quatro repetições. Nas parcelas foram aplicados os tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 11 publications
0
6
1
7
Order By: Relevance
“…The types of water used did not affect the acid detergent fiber (ADF) content. The ADF content obtained, 30.0%, was lower than the values reported by Sanches et al (2016) at 34.5%, Monção et al (2016) at 32%, andPoczynek et al (2016) at 32.5%. This indicates better forage digestibility compared to what the authors observed, since ADF content is inversely proportional to forage maturity.…”
Section: Resultscontrasting
confidence: 56%
See 4 more Smart Citations
“…The types of water used did not affect the acid detergent fiber (ADF) content. The ADF content obtained, 30.0%, was lower than the values reported by Sanches et al (2016) at 34.5%, Monção et al (2016) at 32%, andPoczynek et al (2016) at 32.5%. This indicates better forage digestibility compared to what the authors observed, since ADF content is inversely proportional to forage maturity.…”
Section: Resultscontrasting
confidence: 56%
“…19, e2954 -Taubaté 2024 farming. Nevertheless, the CP content remained higher than the desirable threshold (10%) for ruminant diets and within the range of 14.0% to 16.7% expected for the environmental and soil moisture conditions in the experiment (Sanches et al, 2016;Gonçalves et al, 2018).…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations